Interest Rate Pass Through and the Lessons for the Conduct of Monetary Policy in Tanzania (The Journal of Building and Land Development, 2018)
The aim of this paper is to analyse interest rate pass through of the money market anchor rate to retail bank lending and deposit rates in Tanzania. The Treasury bill rates were used as money market anchor rates. The paper used the monthly time series data for the period of 2008 to 2014. Vector autoregressive model was used to estimate variant models on the interest rate pass through from the money market anchor rate to the retails bank deposit and lending rates. The estimation results revealed that money market anchor rate was passed through to the three and twelve month interest rate in the same period. The size of interest rate pass through for the 364 treasury bills rate was comparable to those of other studies in developing countries. Nonetheless, there was limited pass through from the money market anchor rate to the lending rates. This suggests that limited transmission of the monetary policy to retail lending interest rate due to structural rigidities in the financial markets. Thus, it is recommended that the monetary authority should enhance financial deepening and widening in order to develop new products and enhance competition in the financial markets and monetary transmission mechanism. Keywords: Monetary policy, treasury bill rates, lending rates, deposit rates, liquidity